The development of Turkic studies at Vilnius University - Miškinienė, Galina (Acta Orientalia Vilnensia, 2009)
Institute of the Lithuanian Language At the beginning of the 19th century, the financial possibility to establish a department of Eastern languages at one of the oldest universities in Eastern Europe, Vilnius University, appeared. Turkish was among the Eastern languages that were expected to be taught. The intensive preparation of lecturers was started. Unfortunately, the ambitious plans were destined to never become reality; in 1832 the university was closed. Nevertheless, over the following two centuries the Turkic direction did not disappear; in one form or another it surfaced and retained its vitality. There was a sympathetic environment: Tartars and Karaims—both Turkic ethnic groups—began settling in the Grand Duchy of Lithuania in the 14th century. Vilnius University was the cradle of many famous Orientalists who maintained Turkic research by their activities. In such a way, two main research subjects appeared: Kitabistik and the Karaim language. In this article, the origin problems, development and prospects of Turkic research will be examined.